Pengelolaan Sungai dan Daerah Aliran Sungai (DAS) Guo berbasis Community Driven Program - Nurhamidah Nurhamidah; Alfina Mursida AlJauhari; Tiara Assyifa Muthmainnah; Ahmad Junaidi; Masril Syukur (Warta Pengabdian Andalas, 2025)
Guo River is one of the 3 upstream branches in Kuranji, located at Lubuak Tampuruang in Guo Village RT 01 RW 06 Kuranji Village. As an upstream of Guo Riverr, it has several waterfalls with great potential as an ecotourism area in Padang City. This potential is threatened with failure due to river damage that often occurs every year. The amount of sediment carried during the rainy season and the presence of plants planted by the community on theriverbanks have slowed the water flow and eventually caused sediment to accumulate on the cliffs of the middle section of the Guo River. Sediment accumulation causes changes in the river's flow patterns and narrowing of the river's area. The lack of basic river and watershed management knowledge among the people of Guo Village leads to the degradation of land and river functions, and the low level of public awareness of the dangers of uncontrolled logging underlies the damage to the Guo River. Therefore, community-based structural and non-structural measures are needed to implement river management. Structural actions in this service focus on river management through river normalization, and non-structural actionstakeake the form of Focus Group Discussion (FGD) activities between the community and related stakeholders. The normalization of the Guo River will be carried out by cutting vegetation, removing sedimentation, and strengthening triverbanks.s. Through these activities, it is hoped that the community will be able to use the river and maintain it self-sufficiently.